Understanding parole success following release from prison in England and Wales (2011-2021). - McSweeney, Tim (International Journal of Population Data Science, 2025)
Objectives Parole is a mechanism by which some prisoners in England and Wales may be released from custody under probation supervision and subject to licence conditions. It is the responsibility of the Parole Board to conduct independent risk assessments of eligible prisoners to determine whether they can be safely released. Methods This research involved secondary analysis of de-identified, individual-level records from the Ministry of Justice Data First prisoner custodial journey dataset. The dataset used in this study contained details of 1,113,113 releases from English and Welsh prisons between 1 January 2011 and 29 September 2021 (relating to 614,665 individuals). Results Funded by the Dawes Trust and undertaken in partnership with the Prison Reform Trust, this exploratory, independent study – the largest of its kind to date – describes the parole cohort and reports on the extent and nature of post-release rates of recall, custodial reconviction, and serious further offending by parolees and other prisoners in England and Wales between 2011 and 2021. These outcomes were assessed at one, two, three, five, and ten-year follow-up periods. It also identifies risk and protective factors associated with these outcomes. Conclusion The unique insights from the research will be used to inform a better understanding of how the implementation, development, and delivery of parole arrangements can shape post-release outcomes for prisoners. It will generate public benefits by informing strategies for the effective post-release supervision of prisoners and parolees.